1986
DOI: 10.1002/chin.198642002
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Luminescence and Photophysics of CdS Semiconductor Clusters: The Nature of the Emitting Electronic State.

Abstract: The luminescence of CdS Clusters prepared by arrested precipitation has been studied as function of time, temp., wavelength, and physical size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 1 publication
3
51
1
Order By: Relevance
“…Such transition is often called excitonic [5], because an electron-hole pair generated by light absorption is similar to the Wannier-Mott exciton in a bulk crystal. In this paper, attention is paid to the particles with average sizes d= 2.5…2.8 nm, for which the excitonic Bohr radius (a B =5.4 nm) [6] exceeds a particle size.…”
Section: Absorption Spectroscopymentioning
confidence: 99%
“…Such transition is often called excitonic [5], because an electron-hole pair generated by light absorption is similar to the Wannier-Mott exciton in a bulk crystal. In this paper, attention is paid to the particles with average sizes d= 2.5…2.8 nm, for which the excitonic Bohr radius (a B =5.4 nm) [6] exceeds a particle size.…”
Section: Absorption Spectroscopymentioning
confidence: 99%
“…Other problems which have been treated are the role of surfaces and interfaces, but it is not intended to go into any of these details at this stage [44,45].…”
Section: Theoretical Estimationsmentioning
confidence: 99%
“…E x , D + , and D -will depend upon diameter D. In the purely radiative tunneling decay, close pairs with small R emit faster and at higher energy than distant pairs, for fixed D [44]. Donor and acceptor states can originate not from impurities, but from native defects, namely surface atoms, or vacancies in various configurations [18].…”
Section: Donor-acceptor Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that semiconductor nanocrystals prepared by thermolysis of the precursors in highly coordinating solvents (trioctylphosphine oxide and/or trioctylphosphine) undergo a size distribution focusing process upon slowing the growth and making the growth diffusion controlled [8]. Various methods have been used to control the semiconductor nanocrystal growth in water such as using specific capping agents such as thioglycerol [5,6], alcohols [9] and surfactants [10]. Furthermore, the compartmentalization afforded by the aqueous domains of a water-in-oil microemulsion has shown to be effective [11,12].…”
Section: Introductionmentioning
confidence: 99%